SEED YIELD, OIL CONTENT AND FATTY ACID COMPOSITION OF SOME SESAME GENOTYPES AS INFLUENCED BY SOWING TIME AT SOUTHEAST ANATOLIA IN TURKEY - Öztürk, Ferhat (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
Two field experiments were conducted with two sowing time (early and late) and four sesame genotypes in consecutive in 2014 and 2016 to detect the effect of sowing time and genotypes on yield and quality properties of sesame with different dates of sowing to determine the appropriate sesame genotypes in Southeastern Anatolia of Turkey. The experiment was arranged in a randomized block design with three replications. The results indicated that the highest seed yield was found from Diyarbakir Y -C6 with (1673.35 kg ha(-1)), while the lowest values were produced from Muganli 57 with (1267.46 kg ha(-1)). Regards the quality properties, the variety; 'Diyarbakir Y -C16' (50.09%) and 'Mtiganli 57' (50.71%) as achieved the highest oil content and while; the maximum protein content from Adana Y13 genotypes (24.10%). Manisa white genotype was produced the lowest oil content. The variety 'Manisa white' produced the highest saturated fatty acids, while, the variety 'Muganli 57' was the lowest, although; the variety 'Manisa white' showed the lowest, and variety 'Adana Y13' produced the highest unsaturated fatty acids. The highest oleic/linoleic acid rate was produced by ManisaBeyaz genotypes as 1.19%. The highest of stearic acid was achieved in early sowing time while the highest linoleic acid values were achieved in late sowing time. The highest palmitic acid was produced from Manisa white genotype in early sowing time while the lowest linoleic acid. The high Oleic acid was recorded in early sowing time (45.69%). Overall, our results inferred that the best genotype that could be adopted in this region is Diyarbakir Y -C6, because of its highest seed yield potential. The high Linoleic acid was recorded in late sowing time (40.89%). According to results, it can be concluded that Diyarbakir Y -C6 can be adopted in this region, because of its highest seed yield ability. Further, the genotypes of Diyarbakir Y -C16' and 'Mtiganh 57 which had the maximum oil value but with the lowest saturated fatty acids, variety Adana Y13 which reported the highest protein content and unsaturated fatty acids among other genotypes arc potential varieties to be utilized based on farmer preference.
Keywords: Sesame; Seed yield; Quality; Saturated fatty acid; Unsaturated fatty acids